Regulatory effects of Annulohypoxylon stygium metabolites on the dimorphic transition of Tremella fuciformis - Haichen Huang; Lingli Wei; Jialan Zheng; Shuyu Xing; Yingqi Tang; Silong Chen; Keyan Shen; Jianqiu Chen; Shujing Sun (Food Bioscience, 2026)

A multi-source precipitation blending method combining hydrological model-guided precipitation adjustment and double transfer learning-based data merging - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Jiahua Wei; Yuefei Huang; Shenglong Gu; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

Tracing sources and ecological risks: seasonal-spatial variations of potentially toxic element (PTE) pollution in marine sediments of Beibu Gulf - Zihan Bi; Yao Guan; Linshen Yang; Rongtao Ou; Yilu Gu; Huihua Wei; Xin Liu; Zezhuang Liu; Liping Tian; Keyan Xiao; Siyong Quan; Xuya Peng; et al. (Marine Pollution Bulletin, 2026)

Single-tube duplex isothermal amplification assay for rapid detection of pistachio and cashew allergens - Ruifeng Mao; Yuwen Zhou; Xinru Zhan; Miqi Tan; Yue Sun; Yuanmeng Dong; Keyan Yuan; Yingying Chen; Wei Wang; Dengchao Li; Enjie Diao (Food Control, 2026)

Multi-sensor multi-dimensional data fusion method for submarine cable anchor damage event identification - Chunying Xu; Xinjie Wu; Jingqi Fang; Jianrong Chen; Keyan Xiao; Jiawang Chen; Chuliang Wei; Hailun Fu (Ocean Engineering, 2025)

A runoff prediction approach based on machine learning, ensemble forecasting and error correction: A case study of source area of Yellow River - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Baiyinbaoligao; Jiahua Wei; Jie Gao; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2025)

Targeting ferroptosis in pemphigus vulgaris using aptamer-modified extracellular vesicles - Yishu Tang; Yuxuan Zhang; Hongli Ding; Hao Jin; Liang Zhang; Mao Luo; Keyan Chen; Bin Wei (Chemical Engineering Journal, 2025)

Associations of long-term exposure to fine particulate matter and its components with ovarian aging: Evidence from a cross-sectional study in China - Zifeng Cao; Xinyi Wu; Hongyuan Liu; Keyan Xu; Yehuan Yang; Manting Yang; Daimin Wei; Shidou Zhao; Xue Jiao; Qi Zhao; Ruimin Zheng; Yingying Qin; et al. (Journal of Hazardous Materials, 2025)

Probabilistic Health Risk Assessment and Grading Benchmark Estimation of Atmospheric PM2.5-Bound Heavy Metals in China - Wei Huang; Weilian Sun; Chifei Zhou; Keyan Long; Zunzhen Zhang (Archives of Environmental Contamination and Toxicology, 2025)

Boosting chlorobenzene oxidation over MIL-101(Cr) derived CrOx catalysts: The stepwise regulation of CrOx clusters and oxygen species by calcination atmospheres - Boqiong Jiang; Jun Liu; Keyan Wei; Hanfeng Lu; Xiaole Weng; Jingyi Han; Yi Zhang; Shaocai Yu; Yuhai Sun (Journal of Hazardous Materials, 2025)

Addressing the plastisphere: Sustainable approaches to combat plastic pollution - Wei Xuyang; Khalida Khalil; Tian Zhuo; Chen Keyan; Mohamed Yusuf Mohamed Nazir; Wan Syaidatul Aqma; Niu Qiu Hong (Science of The Total Environment, 2025)

Sexual differentiation and juvenile hermaphroditism in silver pomfrets: Direction, process, and dietary factors - Yaya Li; Mingzhe Yuan; Peng Shi; Keyan Cai; Jiabao Hu; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Zukang Feng; Chunlai Qin; Wei Ge; et al. (Aquaculture, 2024)

Particle-size correlation and prediction models of atmospheric heavy metals - Wei Huang; Weilian Sun; Donglei Sun; Chifei Zhou; Keyan Long; Zunzhen Zhang (Atmospheric Environment, 2024)

Effect of staged thawing assisted antifreeze protein on quality of repeatedly freeze-thawed minced pork - Ying Zhou; Keyan Jing; Chuankang Jia; Rongrong Mao; Baoxue Zhang; Bin Yang; Ci Yuan; Jun Qi; Guoyuan Xiong; Chunhui Zhang; Zhangguo Gao; Wei Xiong (Food Control, 2024)

Spatial–temporal distribution and source analysis of atmospheric particulate-bound cadmium from 1998 to 2021 in China - Wei Huang; Donglei Sun; Tianhe Zhao; Keyan Long; Zunzhen Zhang (Environmental Geochemistry and Health, 2024)

Extracting operation rule of cascade reservoirs using a novel framework considering hydrometeorological spatiotemporal information based on artificial intelligence models - Wei Fang; Hui Qin; Keyan Shen; Xin Yang; Yuqi Yang; Benjun Jia (Journal of Cleaner Production, 2024)

Toxic environmental drug nimesulide detection and degradation using the Bi-functional vanadium and phosphorous doped graphitic carbon nitride nanosheets - Dhanapal Vasu; Arjunan Karthi Keyan; Pichumani Moorthi; Subramanian Sakthinathan; Chung-Lun Yu; Te-Wei Chiu (Journal of Environmental Chemical Engineering, 2023)

Mineral Prospectivity Mapping based on Isolation Forest and Random Forest: Implication for the Existence of Spatial Signature of Mineralization in Outliers - Shuai Zhang; Emmanuel John M. Carranza; Keyan Xiao; Hantao Wei; Fan Yang; Zhenghui Chen; Nan Li; Jie Xiang (Natural Resources Research, 2022)

Overestimated gains in water‐use efficiency by global forests - Xiao Ying Gong; Wei Ting Ma; Yong Zhi Yu; Keyan Fang; Yusheng Yang; Guillaume Tcherkez; Mark A. Adams (Global Change Biology, 2022)
Increases in terrestrial water‐use efficiency (WUE) have been reported in many studies, pointing to potential changes in physiological forcing of global carbon and hydrological cycles. However, gains in WUE are of uncertain magnitude over longer (i.e. >10 years) periods of time largely owing to difficulties in accounting for structural and physiological acclimation. 13 C signatures (i.e. δ 13 C) of plant organic matter have long been used to estimate WUE at temporal scales ranging from days to centuries. Mesophyll conductance is a key uncertainty in estimated WUE owing to its influence on diffusion of CO 2 to sites of carboxylation. Here we apply new knowledge of mesophyll conductance to 464 δ 13 C chronologies in tree‐rings of 143 species spanning global biomes. Adjusted for mesophyll conductance, gains in WUE during the 20th century (0.15 ppm year −1 ) were considerably smaller than those estimated from conventional modelling (0.26 ppm year −1 ). Across the globe, mean sensitivity of WUE to atmospheric CO 2 was 0.15 ppm ppm −1 . Ratios of internal‐to‐atmospheric CO 2 (on a mole fraction basis; c i / c a ) in leaves were mostly constant over time but differed among biomes and plant taxa—highlighting the significance of both plant structure and physiology. Together with synchronized responses in stomatal and mesophyll conductance, our results suggest that ratios of chloroplastic‐to‐atmospheric CO 2 ( c c / c a ) are constrained over time. We conclude that forest WUE may have not increased as much as previously suggested and that projections of future climate forcing via CO 2 fertilization may need to be adjusted accordingly.

Estimation of the Interaction Between Groundwater and Surface Water Based on Flow Routing Using an Improved Nonlinear Muskingum-Cunge Method - Chengpeng Lu; Keyan Ji; Wanjie Wang; Yong Zhang; Tema Koketso Ealotswe; Wei Qin; Jiayun Lu; Bo Liu; Longcang Shu (Water Resources Management, 2021)

Geochemically Constrained Prospectivity Mapping Aided by Unsupervised Cluster Analysis - Shuai Zhang; Emmanuel John M. Carranza; Keyan Xiao; Zhenghui Chen; Nan Li; Hantao Wei; Jie Xiang; Li Sun; Yang Xu (Natural Resources Research, 2021)

Mapping and identification of CsSh5.1, a gene encoding a xyloglucan galactosyltransferase required for hypocotyl elongation in cucumber (Cucumis sativus L.) - Keyan Zhang; Junsong Pan; Yue Chen; Ying Wei; Hui Du; Jingxian Sun; Duo Lv; Haifan Wen; Huanle He; Gang Wang; Run Cai (Theoretical and Applied Genetics, 2021)

Data-driven Mineral Prospectivity Mapping by Joint Application of Unsupervised Convolutional Auto-encoder Network and Supervised Convolutional Neural Network - Shuai Zhang; Emmanuel John M. Carranza; Hantao Wei; Keyan Xiao; Fan Yang; Jie Xiang; Shihong Zhang; Yang Xu (Natural Resources Research, 2021)